The Self-Simulation Hypothesis Interpretation of Quantum Mechanics - Klee Irwin; Marcelo Amaral; David Chester (Entropy, 2020)
We modify the simulation hypothesis to a self-simulation hypothesis, where the physical universe, as a strange loop, is a mental self-simulation that might exist as one of a broad class of possible code theoretic quantum gravity models of reality obeying the principle of efficient language axiom. This leads to ontological interpretations about quantum mechanics. We also discuss some implications of the self-simulation hypothesis such as an informational arrow of time.